The Impact of the EC's Internal Marketon Nonmember Countries : The Case of EFTA. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper presents an overview of the impact of the EC's Internal Market on the EFTA countries. It starts by examining the history of EC-EFTA relations; the institutional and legal changes that closer cooperation may require; and the general implications of the Internal Market Program for EFTA countries. This is followed by an exploration of specific issues relating to the goods trade, transport services, labor mobility, financial services and capital flows. Subsequent chapters focus on the potential impact of the EC's proposed monetary unification on EFTA countries and the implications of the EC's efforts in the area of tax harmonization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet